Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Certainly! Let's solve the quadratic equation [tex]\( x^2 + 9x + 9 = 0 \)[/tex] step-by-step.
### Step 1: Identify the coefficients
First, identify the coefficients [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] from the quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex].
For the equation [tex]\( x^2 + 9x + 9 = 0 \)[/tex]:
- [tex]\(a = 1\)[/tex]
- [tex]\(b = 9\)[/tex]
- [tex]\(c = 9\)[/tex]
### Step 2: Calculate the discriminant
The discriminant of a quadratic equation is given by [tex]\( \Delta = b^2 - 4ac \)[/tex].
Substitute the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:
[tex]\[ \Delta = 9^2 - 4 \times 1 \times 9 \][/tex]
[tex]\[ \Delta = 81 - 36 \][/tex]
[tex]\[ \Delta = 45 \][/tex]
### Step 3: Determine the roots
The roots of the quadratic equation can be found using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
Substitute [tex]\(a = 1\)[/tex], [tex]\(b = 9\)[/tex], and [tex]\(\Delta = 45\)[/tex]:
[tex]\[ x_1 = \frac{-9 + \sqrt{45}}{2 \times 1} \][/tex]
[tex]\[ x_2 = \frac{-9 - \sqrt{45}}{2 \times 1} \][/tex]
### Step 4: Simplify the roots
Since [tex]\(\sqrt{45}\)[/tex] can be written as [tex]\(\sqrt{9 \times 5} = 3\sqrt{5}\)[/tex]:
[tex]\[ x_1 = \frac{-9 + 3\sqrt{5}}{2} \][/tex]
[tex]\[ x_2 = \frac{-9 - 3\sqrt{5}}{2} \][/tex]
### Final Answer
Therefore, the solutions to the quadratic equation [tex]\( x^2 + 9x + 9 = 0 \)[/tex] are:
[tex]\[ x_1 = -1.1458980337503153 \][/tex]
[tex]\[ x_2 = -7.854101966249685 \][/tex]
This numerical evaluation confirms it: The correct choice among the given options is
[tex]\[ \frac{-9 \pm 3 \sqrt{5}}{2} \][/tex].
### Step 1: Identify the coefficients
First, identify the coefficients [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] from the quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex].
For the equation [tex]\( x^2 + 9x + 9 = 0 \)[/tex]:
- [tex]\(a = 1\)[/tex]
- [tex]\(b = 9\)[/tex]
- [tex]\(c = 9\)[/tex]
### Step 2: Calculate the discriminant
The discriminant of a quadratic equation is given by [tex]\( \Delta = b^2 - 4ac \)[/tex].
Substitute the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex]:
[tex]\[ \Delta = 9^2 - 4 \times 1 \times 9 \][/tex]
[tex]\[ \Delta = 81 - 36 \][/tex]
[tex]\[ \Delta = 45 \][/tex]
### Step 3: Determine the roots
The roots of the quadratic equation can be found using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{\Delta}}{2a} \][/tex]
Substitute [tex]\(a = 1\)[/tex], [tex]\(b = 9\)[/tex], and [tex]\(\Delta = 45\)[/tex]:
[tex]\[ x_1 = \frac{-9 + \sqrt{45}}{2 \times 1} \][/tex]
[tex]\[ x_2 = \frac{-9 - \sqrt{45}}{2 \times 1} \][/tex]
### Step 4: Simplify the roots
Since [tex]\(\sqrt{45}\)[/tex] can be written as [tex]\(\sqrt{9 \times 5} = 3\sqrt{5}\)[/tex]:
[tex]\[ x_1 = \frac{-9 + 3\sqrt{5}}{2} \][/tex]
[tex]\[ x_2 = \frac{-9 - 3\sqrt{5}}{2} \][/tex]
### Final Answer
Therefore, the solutions to the quadratic equation [tex]\( x^2 + 9x + 9 = 0 \)[/tex] are:
[tex]\[ x_1 = -1.1458980337503153 \][/tex]
[tex]\[ x_2 = -7.854101966249685 \][/tex]
This numerical evaluation confirms it: The correct choice among the given options is
[tex]\[ \frac{-9 \pm 3 \sqrt{5}}{2} \][/tex].
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.